Development of a proposed solutions box for improving nutritional behaviors of female school students: Protocol of a mixed-method study - Nasrin Mehrjoyan; Fatemeh Zarei; Fazlollah Ghofranipour; Fazlollah Ahmadi (PLoS ONE, 2025)
Aim Adolescent girls in Iran face significant challenges related to poor nutritional behaviors, such as inadequate fruit and vegetable consumption, high intake of processed foods, and irregular meal patterns. These behaviors contribute to long-term health risks, including obesity and micronutrient deficiencies. ‘The aim of this study is to develop an evidence-based, context-specific ‘solution box’ to improve the nutritional behaviors of female school students in Khuzestan province. Design A mixed-method study using a sequential exploratory design (Creswell model). Methods This research will be conducted in three distinct stages. Stage 1: Qualitative Phase –Part A: A qualitative study using directed content analysis based on Social Cognitive Theory will be conducted. This phase will involve focus groups and interviews with female students, parents, and stakeholders to identify barriers to healthy eating and propose context-specific solutions. Part B: The perceived solutions will be extracted and categorized based on their relevance and feasibility. Stage 2: Quantitative Phase – Part A: Extracted solutions will be prioritized using the nominal group technique. Part B: Prioritized solutions will be ranked using a pairwise comparison scoring method. Stage 3: Solutions Optimization – Part A: A matrix of solutions will be developed based on theoretical frameworks. Part B: An action plan for implementing the solutions will be created. Part C: The solutions will be visualized on a digital platform for accessibility and usability. Results Not applicable for the protocol study.